Perception of Dental, Medical, and Nursing Students on the Use of Simulation-Based Training in Clinical Skills. - Kulshrestha, Navya; Kumar, Kundan; Sherawat, Vinima; Bhati, Jai; Rathi, Heena; Singh, Vaibhav; Garg, Hemant Kumar; Mohan, Brij (Journal of Neonatal Surgery, 2025)
Background: Simulation-based training (SBT) is increasingly used in health professions education to improve clinical skills in a safe environment. This cross-sectional study assessed and compared perceptions of SBT among undergraduate dental (BDS), medical (MBBS), and nursing students. Methods: A structured questionnaire including a 5-point Likert scale (1 = strongly disagree to 5 = strongly agree) measuring overall perception/acceptability of SBT and specific domains (realism, usefulness for skill acquisition, confidence building, preference for future use) was administered to 30 BDS, 100 MBBS, and 50 Nursing students (N = 180). Descriptive statistics, one-way ANOVA for mean score comparisons, and proportion tests for favorable responses (score ≥4) were used. Significance was set at α = 0.05. Results: Mean overall perception scores (mean ± SD) were: BDS 3.71 ± 0.46; MBBS 4.08 ± 0.47; Nursing 4.04 ± 0.47. One-way ANOVA showed a significant difference between groups (F = 7.41, p = 0.0008). Proportion of students with favorable perception (score ≥4): BDS 30.0% (9/30), MBBS 61.0% (61/100), Nursing 62.0% (31/50). Pairwise proportion tests showed MBBS and Nursing students had significantly higher favorable proportions than BDS students (BDS vs MBBS p = 0.0028; BDS vs Nursing p = 0.0056). MBBS and Nursing did not differ significantly (p = 0.906). Conclusions: MBBS and Nursing students reported more positive perceptions of SBT than BDS students in this sample. Implementation strategies to improve engagement and perceived relevance for dental undergraduates are recommended